Pengaruh Edukasi Media Leaflet Terhadap Penggunaan Alat Pelindung Diri (APD) Pada Petugas Pengangkut Sampah Di UPT TPA Tamangapa Antang - Asriani, Cici; Baharuddin, Alfina; Ulmy Mahmud, Nur (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2025)
Waste transportation is an activity that starts from the collection process and continues with the transportation of waste. The problem in this study is related to the influence of leaflet media education on waste collectors' knowledge, attitudes, and actions. This study aims to determine the effect of leaflet media education on waste collectors' knowledge, attitudes, and actions regarding using Personal Protective Equipment (PPE). This type of research is quantitative with a